Serological inference of past primary and secondary dengue infection: implications for vaccination. Issue 156 (26th July 2019) - Lam, Ha Minh; Phuong, Huynh Thi; Thao Vy, Nguyen Ha; Le Thanh, Nguyen Thi; Dung, Pham Ngoc; Ngoc Muon, Thai Thi; Van Vinh Chau, Nguyen; Rodríguez-Barraquer, Isabel; Cummings, Derek A. T.; Wills, Bridget A.; Boni, Maciej F.; Rabaa, Maia A.; et al.
Abstract : Owing to the finding that Dengvaxia ® (the only licensed dengue vaccine to date) increases the risk of severe illness among seronegative recipients, the World Health Organization has recommended screening individuals for their serostatus prior to vaccination. To decide whether and how to carry out screening, it is necessary to estimate the transmission intensity of dengue and to understand the performance of the screening method. In this study, we inferred the annual force of infection (FOI; a measurement of transmission intensity) of dengue virus in three locations in Vietnam: An Giang (FOI = 0.04 for the below 10 years age group and FOI = 0.20 for the above 10 years age group), Ho Chi Minh City (FOI = 0.12) and Quang Ngai (FOI = 0.05). In addition, we show that using a quantitative approach to immunoglobulin G (IgG) levels (measured by indirect enzyme-linked immunosorbent assays) can help to distinguish individuals with primary exposures (primary seropositive) from those with secondary exposures (secondary seropositive). We found that primary-seropositive individuals—the main targets of the vaccine—tend to have a lower IgG level, and, thus, they have a higher chance of being misclassified as seronegative than secondary-seropositive cases. However, screening performance can be improved by incorporating patient age and transmission intensity into the interpretation of IgG levels.